Starting a business all-in-one for dummies - Allen, Kathleen R. (Hoboken, NJ John Wiley & Sons, Inc., 2015)
The book compilation in this volume covers entrepreneurship, business plan development, initiating an online business, franchising and home-based businesses, bookkeeping and accounting, financial management, employee management, and marketing/branding.
Book I. From idea to reality -- Book II. Planning your business -- Book III. Managing your finances -- Book IV. Managing your business -- Book V. Marketing and promotion.
Includes index.
"8 books in 1"--Cover.
Keywords: New business enterprises -- Management; Business planning; Small business -- Planning